Progressive glacial retreat in the Southern Altiplano (Uturuncu volcano, 22°S) between 65 and 14 ka constrained by cosmogenic 3He dating. Issue 1 (July 2014) - Blard, Pierre-Henri; Lave, Jérôme; Farley, Kenneth A.; Ramirez, Victor; Jimenez, Nestor; Martin, Léo C.P.; Charreau, Julien; Tibari, Bouchaïb; Fornari, Michel
Abstract: This work presents the first reconstruction of late Pleistocene glacier fluctuations on Uturuncu volcano, in the Southern Tropical Andes. Cosmogenic 3 He dating of glacial landforms provides constraints on ancient glacier position between 65 and 14 ka. Despite important scatter in the exposure ages on the oldest moraines, probably resulting from pre-exposure, these 3 He data constrain the timing of the moraine deposits and subsequent glacier recessions: the Uturuncu glacier may have reached its maximum extent much before the global LGM, maybe as early as 65 ka, with an equilibrium line altitude (ELA) at 5280 m. Then, the glacier remained close to its maximum position, with a main stillstand identified around 40 ka, and another one between 35 and 17 ka, followed by a limited recession at 17 ka. Then, another glacial stillstand is identified upstream during the late glacial period, probably between 16 and 14 ka, with an ELA standing at 5350 m. This stillstand is synchronous with the paleolake Tauca highstand. This result indicates that this regionally wet and cold episode, during the Heinrich 1 event, also impacted the Southern Altiplano. The ELA rose above 5450 m after 14 ka, synchronously with the Bolling–Allerod.